EXPLORING INTERACTIVE READ-ALOUD PRACTICES IN EXPANDING VOCABULARY KNOWLEDGE IN BOJONEGORO LITERACY COMMUNITY - Meiga Ratih Tirtanawati; Masnuatul Hawa; Oktha Ika Rahmawati; Faiqotus Silfia Almiftah (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
This study explores the role of interactive the read-aloud strategy in expanding vocabulary knowledge among members of the Bojonegoro Literacy Community in East Java, Indonesia. Interactive read-aloud activities remain important in community literacy contexts because they promote collaborative learning, oral interaction, listening comprehension, and shared meaning-making. These activities also support discussion, pronunciation modeling, and vocabulary development through social engagement. Using a mixed-method design, the research involved 89 participants from four literacy communities: Kampung Sinau, ABE (Angkringan Buku Emperan), Forum TBM Bojonegoro, and Read Aloud Bojonegoro. This member was considered sufficient for this mixed-method community-based study because the research aimed to obtain quantitative trends and qualitative insights rather than generalize findings to a larger population. Quantitative data were collected through pre-test and post-test vocabulary assessments, while qualitative data were obtained from observations, interviews, and facilitator reflections. The findings reveal significant improvements in vocabulary scores across all groups, with Read Aloud Bojonegoro achieving the highest gain. Paired-samples t-tests revealed statistically significant gains in vocabulary scores across all groups (p < .05), with effect sizes ranging from moderate to large (Cohen's d = 0.72–1.38). Read Aloud Bojonegoro achieved the highest mean gain of 27 points (pre-test M = 53; post-test M = 80), while Forum TBM Bojonegoro recorded a gain of 24 points. Qualitative findings revealed that read-aloud activities supported vocabulary growth, pronunciation development, and learner engagement. The strategy's effectiveness was shaped by facilitation quality, session structure, and active participation, while also fostering reading motivation. These results align with recent research demonstrating that interactive read-aloud activities foster vocabulary development via meaningful contextual exposure, dialogue, and active language use.